Concentrações séricas de vitamina D e disfunção orgânica em pacientes com sepse grave e choque séptico - Alves, Fernanda Sampaio [UNIFESP] (2016)
Vitamin D is important to the immunomodulation and regulation of inflammatory response. Nevertheless, vitamin D deficiency is rarely taken into account in critically ill patients and its relation with worse outcomes is uncertain. We aimed to assess the baseline serum levels of vitamin D and its variation after the first 7days in septic and non- septic patients and to correlate them with the degree of organ dysfunction both at inclusion and after the first seven days. This was a prospective, observational study in critically ill patients ?18 years-old with severe sepsis or septic shock. We also included a control group paired by age and degree of organ dysfunction.. We determined serum vitamin D levels at baseline (D0) and after the seventh day (D7). Septic and non-septic patients were categorized according to the improvement of vitamin D levels. We consider severe deficiency values below 10 ng/mL, deficiency values between 10 and 20 ng/mL, insufficiency values between 20 and 30 ng/mL and sufficiency if they were ? 30 ng/mL. We also assess clinical and laboratory data to determine the Sequential Organ Failure Assessment score on D0 and D7 and its variation. We considered significant results at p < 0.05. We included 51 patients, 26 with sepsis and 25 controls. The prevalence of hypovitaminosis D was 98%, with no significant difference between septic and non-septic patients. There was no significant correlation between vitamin D at D0 and the Sequential Organ Failure Assessment score at D0 or its variation after 7 days., There was no correlation between the variation of vitamin D and the variation of organ dysfunction, neither in general population nor in septic patients. The baseline levels of vitamin D weakly correlated with D0 magnesium levels (r = 0.387). The improvement in vitamin D levels was higher in the sepsis group. Patients who improved classification of vitamin D also had improved the Sequential Organ Failure Assessment score at D7 (p = 0.013). In conclusion, the prevalence of vitamin D deficiency was high in critically ill patients, both septic and non-septic ones. Septic patients had a greater improvement in their vitamin D levels after 7th days as compared with the non-septic patients. Those critically ill patients who improved from their vitamin D deficiency also had a greater reduction in the intensity of organ dysfunction after 7 days.